Trauma [compact disc, unabridged] : a novel - Palmer, Michael, 1942-2013 (Macmillan Audio, 2015)
Dr. Carrie Bryant's four years as a neurosurgical resident at White Memorial Hospital have earned her the respect and admiration of peers and staff alike. When given the chance to perform her first unsupervised brain surgery, Carrie jumps at the opportunity. What should have been a routine, hours-long operation turns horribly wrong and jeopardizes her patient's life. Emotionally and physically drained, Carrie is rushed back to the OR to assist in a second surgery.